Clarifying the concept of avoidable emergency department attendance. Issue 1 (January 2021) - Parkinson, Beth; Meacock, Rachel; Checkland, Katherine; Sutton, Matt
Emergency department attendances are rising in several countries. Many of the policies aimed at reducing emergency department attendances are based on the assumption that a proportion of current utilization is 'avoidable' and therefore could be reduced. In considering how to achieve this aim, it is important to first understand the problem. In this essay, we review the literature on the concept and identification of avoidable emergency department attendances in England. We identified three areas of inconsistency surrounding avoidable emergency department attendances: the terminology, the underlying definition, and the method used to identify avoidable attendances. We offer a more nuanced definition which may better support action to reduce emergency department activity. Recognizing that there are different types of undesirable utilization which vary by underlying causes and potential solutions will aid policy makers in identifying areas where policies targeting reductions in emergency department attendances would best be directed.